Subjective experience of depressed mood among medical students at the University of Pretoria - L van Niekerk; A J Viljoen; P Rischbieter; Lindi Scribante (South African Journal of Psychiatry, 2008)
Introduction. Following the suicide of a 4th-year medicalstudent, questions were raised as to whether medicalstudents are more vulnerable to depression and suicide thantheir counterparts studying other courses at the University ofPretoria. A literature search revealed that medical students anddoctors run a higher risk for suicide than other students andprofessions. Method. A questionnaire was devised and distributed tomedical students and a control group of other students, askingabout feelings of despair/hopelessness, suicide ideation andprevious attempts, knowledge regarding support structuresprovided by the university, and willingness to use thesestructures. Results. Both groups of students responded similarly to allquestions. Frequency of diagnosed psychiatric illness, use ofmedication, and suicidal thoughts and attempts did not differsignificantly. Both groups of students were unaware of supportservices offered by the university, and both were unwilling toutilise such services. The students seemed to have high ratesof depression in comparison with prevalence data from othercountries. Conclusion. Attempts to improve support for medical studentsshould address students’ awareness of available supportstructures and their willingness to utilise them.